Examining the effect of employee green involvement on perception of corporate social responsibility: Moderating role of green training. Issue 1 (14th January 2019) - Srivastava, Anugamini Priya; Shree, Sonal
Abstract : Purpose: The purpose of this paper is to understand the extent to which green involvement (GI) can affect employee perception of corporate social responsibility (CSR), with the intervening role of green training (GT). Design/methodology/approach: The sample for the study was collected from employees working in tourist hotels. Exploratory factor analysis and confirmatory factor analysis was conducted to assess the fit of the hypothesized model, and hierarchical regression analysis to test the hypothesis. Findings: The results showed that GI of employees has a positive and significant relationship with their perception of CSR. The study further revealed that when there is an increase in GT, the relationship between GI and perception of CSR gets more positive. Originality/value: It adds value to the ongoing research in the field of environment, training and CSR. The findings will be helpful for policy makers and researchers in the field of stakeholder management.